Penerapan Metode Analytical Hierarchy Process Untuk Menentukan Jasa Pengiriman Pada PT. Kharisma Yona Mulia - Ernawati, Siti; Alfahran Islami, Hasby (Jurnal Teknik Informatika UNIKA Santo Thomas, 2022)
Delivery services are one of the most important things in the company’s business process in the warehousing service sector. The warehouse company stores goods from the seller so that they are stored properly and sent to delivery service when there is an order for goods from the seller. Companies that run in the field of warehousing services, on of which is PT. Kharisma Yona Mulia. PT. Kharisma Yona Mulia is still having problems in determining the best shipping services to be more rational. The AHP method is a process of comparing criteria into alternatives, if the resulting value is higher, the higher the priority for delivery service to choose. The criteria used in this study are shipping costs, delivery speed, delivery security, services and facilities. There are alternatives that are used, namely JNT, JNE, TIKI and SICEPAT. By using the AHP method for determining the delivery service, the results of the order of criteria values are obtained, namely delivery security 0.434 0r 43.4%, shipping costs 0.264 or 26.4%, delivery speed 0.160 or 16%, service 0.091 or 9.1% and 0.051 or 5.1% facilities. Then the results obtained the largest value for the alternative is TIKI with a value of 0.39 or 39%.